What determines environmental proactiveness in the Indian cement sector? An empirical study. (10th October 2019) - Vishwakarma, Arun Kumar; Nema, Arvind K.; Sangle, Shirish
Abstract: The lack of clarity in the environmental strategies has created uncertainty towards industrial efforts to protect the environment. However, some firms are more apprehensive regarding environmental protection in comparison to their counterparts. What determines the environmental proactiveness of these firms which go beyond extant laws to adopt proactive environmental strategies (PES)? This article, through an empirical study of the Indian cement sector, identifies the determinants of adoption of PES. Quantitative analysis of survey data from 310 respondents identifies four determinants; organisational capability, market benefits, stakeholder pressure, and environmental risk management. Four hypotheses are proposed to test the Confirmatory Factor Analysis (CFA) outcome. Organisational capability and market benefits are observed to be the key determinants. The study determines the strength of the identified determinants on PES adoption using structural equation modelling (SEM) and path analysis. Path analysis ranks the determinants in the order; organisational capability, market benefits, environmental risk management and stakeholder pressure. The evidence based findings from the research are expected to be useful for the environmental management practitioners as well as academicians. On the global front, the developing countries having identical socio-economic and political structure may gain from the findings of the study. Highlights: Emissions from the cement sector in India, which is one of the most emission intensive industry is a major cause of concern. Cement companies go beyond environmental regulations to adopt proactive environmental strategies (PES). The study uses statistical analysis to identify determinants of adoption of PES. Path analysis ranks organisational capability and market benefits as the two strongest determinants. The other two determinants identified are environmental risk management and stakeholder pressure.